2012
DOI: 10.1021/la301399a
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Nitrile-Terminated Biphenylthiol Self-Assembled Monolayers by Electron Irradiation and Related Applications

Abstract: Here we describe the behavior of self-assembled monolayers (SAMs) of 4'-cyanobiphenyl-4-thiol (CBPT) on Au(111) upon electron irradiation. Under such a treatment, the aromatic framework of CBPT SAMs is laterally cross-linked while the nitrile groups, located at the SAM-ambience interface, are reduced to active amine moieties which can be used as docking sites for the coupling of other species. This makes CBPT monolayers as a promising system for conventional and chemical lithography as well as for nanofabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…56,61,62 Cross-linking was reported for aromatic SAMs under electron irradiation at 10 eV, 24,63 50 eV 8,25,27,28,30,64,65 and higher energies. 29,66 The mechanisms proposed involve primary and secondary electrons that are emitted from the SAM-substrate system, 67 which cause C-H bond breaking within the film. The partially dehydrogenated molecules relax then by forming single and double CC bonds between adjacent phenyl rings, forming a 2D network.…”
Section: Resultsmentioning
confidence: 99%
“…56,61,62 Cross-linking was reported for aromatic SAMs under electron irradiation at 10 eV, 24,63 50 eV 8,25,27,28,30,64,65 and higher energies. 29,66 The mechanisms proposed involve primary and secondary electrons that are emitted from the SAM-substrate system, 67 which cause C-H bond breaking within the film. The partially dehydrogenated molecules relax then by forming single and double CC bonds between adjacent phenyl rings, forming a 2D network.…”
Section: Resultsmentioning
confidence: 99%
“…106,108 SAMs of rigid molecular moieties, in which the polar groups attached to them or incorporated in them with fixed directions, provide attractive alternatives. [109][110][111] Many of these rigid structures are linked aromatics with extended π-conjugation.…”
Section: R a F Tmentioning
confidence: 99%
“…PS, poly(4‐vinyl pyridine), and PMMA were then subsequently grown from the surface through SIPGP . Increasing brush thickness, regulated by longer polymerization times or higher e‐beam doses, produced films with greater buckling amplitude. The results showed that the brush morphologies were reversibly responsive to external triggers (solvent and pH) and demonstrated buckling and changes in film properties (optical and wetting).…”
Section: Detached Polymer Filmsmentioning
confidence: 99%